KEBERFUNGSIAN KELUARGA ANAK KORBAN EKSPLOITASI DI KAWASAN MARPOYAN DAMAI KOTA PEKANBARU - Tresno, Joko; Umari, Tri; Putra, Roby Maiva (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to determine and describe the profile of the family functioning of children victims of exploitation in the peaceful marpoyan area of Pekanbaru city in terms of the identity of children victims of exploitation as well as knowing and describing the functioning of the families of children victims of exploitation in the peaceful marpoyan area of Pekanbaru city. This research uses descriptive research with a qualitative approach. The subjects in this study were 4 child victims of exploitation who were taken using the Accidental Sampling technique. The results showed that the profile of child victims of exploitation in the peaceful marpoyan area of Pekanbaru city has an age range of 16-17 years, from 4 children 3 children working as street singers. and the rest as newspaper sellers. Some children victims of exploitation in the peaceful marpoyan area of Pekanbaru city still live with their parents and some others live with their biological brothers or friends. And the functioning of the families of children who are victims of exploitation in the peaceful marpoyan area of Pekanbaru city, from 4 children, none of them are carried out by all 7 functions in the family. Only a few functions are fulfilled, there is even one child who is not carried out at all. In a good family, the seven functions should be carried out, if one of these functions is not carried out it will have an impact on the harmony of family members, especially the child.Key Words: Function Of The Family, The Victims Children Exploitation